2020
DOI: 10.3390/cells9092023
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking of HBV Particles

Abstract: The human hepatitis B virus (HBV), that is causative for more than 240 million cases of chronic liver inflammation (hepatitis), is an enveloped virus with a partially double-stranded DNA genome. After virion uptake by receptor-mediated endocytosis, the viral nucleocapsid is transported towards the nuclear pore complex. In the nuclear basket, the nucleocapsid disassembles. The viral genome that is covalently linked to the viral polymerase, which harbors a bipartite NLS, is imported into the nucleus. Here, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 170 publications
(222 reference statements)
0
61
0
4
Order By: Relevance
“…Moreover, it has been shown that the machinery involved in the endocytosis of epidermal growth factor receptor (EGFR), which acts as a cofactor for HBV entry, is also involved in the internalization and transport in the endosomal network of HBV [ 26 , 27 ]. The mechanisms leading to HBV escape from endosomes are not yet fully understood, and membrane fusion may be mediated by the fusogenic domains identified in the different surface proteins L, M, and S [ 7 , 28 ].…”
Section: Virus Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been shown that the machinery involved in the endocytosis of epidermal growth factor receptor (EGFR), which acts as a cofactor for HBV entry, is also involved in the internalization and transport in the endosomal network of HBV [ 26 , 27 ]. The mechanisms leading to HBV escape from endosomes are not yet fully understood, and membrane fusion may be mediated by the fusogenic domains identified in the different surface proteins L, M, and S [ 7 , 28 ].…”
Section: Virus Entrymentioning
confidence: 99%
“…Upon infection, the rcDNA intermediate form is repaired so as to give rise to a complete double stranded covalently closed circular DNA (cccDNA) that is located in the nucleus and serves as a template for the transcription of all viral RNAs, including pgRNA [ 5 , 6 ]. In the cytoplasm, after reverse transcription, mature capsids containing rcDNA assemble with the viral envelope at the cellular multivesicular body, allowing for the formation and secretion of viral particles ( Figure 1 ) [ 7 , 8 , 9 ]. Alternatively, capsids can return directly to the nucleus, resulting in intracellular cccDNA amplification [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that circRNAs can competitively bind to microRNAs and RBPs, serving as RBP sponges and transporters for speci c molecules [33]. circRNAs have also been shown to be transported in exosomes by RBPs towards multivesicular bodies [34]. Related to our main objective, circDym, a conserved circRNA isoform derived from Dym, has been discovered to function as a microRNA sponge by binding to miR-9 and miR-346 and regulates protein synthesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant viral antigen in the blood is HBsAg, which plays an important role in preventing immune control of HBV [ 8 , 30 ]. Circulating HBsAg is almost entirely in the form of non-infectious HBV subviral particles (SVPs) [ 31 , 32 , 33 ].…”
Section: Targets For An Hbv Curementioning
confidence: 99%
“…In the cytoplasm of HBV-infected hepatocytes, the nucleocapsid is transported through the nuclear pore complex by microtubule-mediated transport. Following capsid dissociation via unknown factors, rcDNA is released into the nucleus and is converted to cccDNA by host factors, forming a stable mini-chromosome [ 7 , 8 ]. The cccDNA is transcribed into pregenomic RNA (pgRNA), which is translated to the nucleocapsid protein and the HBV DNA polymerase and serves thereafter as the template for rcDNA synthesis.…”
Section: Introductionmentioning
confidence: 99%